2017
DOI: 10.1007/s00787-017-1075-y
|View full text |Cite
|
Sign up to set email alerts
|

Children’s and parent’s psychological profiles in selective mutism and generalized anxiety disorder: a clinical study

Abstract: Selective mutism (SM) is classified in DSM-5 as an anxiety disorder. The aim of the study was to investigate the psychological features of children with SM and their parental psychological profiles, compared to generalized anxiety disorder (GAD) children and their parents. The parents of 26 preschool children with SM and 32 with children with GAD filled out the child behavior check list for 1½-5 years (CBCL1½-5) and the symptom checklist-90-revised (SCL-90-R). Information about the children and their parents' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 40 publications
0
17
0
1
Order By: Relevance
“…Two studies found associations between paternal psychopathology and SM, but not maternal psychopathology [7,8]. A recent study found that the mothers of children with SM displayed more obsessive-compulsive features and fathers exhibited more phobic anxiety symptoms than the parents of children with generalized anxiety disorder [9]. There have been findings of higher rates of maternal schizoid and schizotypal features [10], increased levels of parental anxiety [8,10] and social anxiety among the parents of children with SM [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies found associations between paternal psychopathology and SM, but not maternal psychopathology [7,8]. A recent study found that the mothers of children with SM displayed more obsessive-compulsive features and fathers exhibited more phobic anxiety symptoms than the parents of children with generalized anxiety disorder [9]. There have been findings of higher rates of maternal schizoid and schizotypal features [10], increased levels of parental anxiety [8,10] and social anxiety among the parents of children with SM [11].…”
Section: Introductionmentioning
confidence: 99%
“…To address the role of comorbidity, we also report comorbid diagnoses for the SM cases in the study sample. Based on previous findings showing higher rates of parental psychopathology in several different diagnostic categories [9][10][11]21], the study hypothesis was that there would be higher rates of psychiatric morbidity among the parents of children with SM compared to the controls. In addition, we hypothesized that both advanced and young parental age would be associated with SM, as seen with behavioural and emotional disorders of childhood [14].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Capozzi, Manti, Dio Trani, Romani, Vigliante, and Sotos [7], 58 preschool children with SM or generalized anxiety disorder (GAD) and their parents were evaluated at a pediatric clinic over a period of five years. Child and family variables did not discriminate children in the SM and GAD groups.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by the child’s significant inability to speak in specific social situations (for instance at school) or in non-familiar circumstances. The clinical and research data confirm that SM is a complex etiological multifactorial disorder whose maintenance is connected with the interaction of biological (familiarity with shyness, preterm birth) ( Capobianco & Cerniglia, 2017) and environmental early factors (anxiety and overprotectiveness of the mother) ( Capobianco et al , 2010; Capobianco et al , 2017; Capozzi et al ., 2017; Pizzuto & Capobianco, 2008) Analysis of the underlying thoughts and emotions in mutacic behavior reveals fear of judgment, fear of failure and being mocked, shame, depression, feelings of worthlessness or inadequacy , catastrophizing, and confirms the comorbidity between selective mutism and internalizing symptoms. The typical age of onset for selective mutism is between 3–6 years, even though the disorder gets usually diagnosed belatedly during the school age (around 7–8 years).…”
Section: Introductionmentioning
confidence: 76%